2007
DOI: 10.1111/j.1439-0442.2007.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Findings in Porcine Hearts After Extracorporeal Long‐term Preservation with a Modified Langendorff Perfusion System

Abstract: Preserved ultrastructure is an important precondition for functional regeneration after heart transplantation. We investigated the effectiveness of a newly developed modified Langendorff system in extracorporeal heart perfusion. (Experiment I) Cardioplegia and cold ischaemia were performed in six pigs. Hearts were connected to a modified Langendorff system, and perfused with leucocyte depleted autologous blood. (Experiment II) The untreated hearts of three healthy pigs served as controls. Forty-seven myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…, , Aupperle et al . ) have been reported. Such findings are signs of alterations in mitochondrial function, which again likely affects cardiac contractility.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…, , Aupperle et al . ) have been reported. Such findings are signs of alterations in mitochondrial function, which again likely affects cardiac contractility.…”
Section: Discussionmentioning
confidence: 94%
“…Ca 2+ overload may induce cardiac contractile dysfunction through different pathways. In hypothermia and rewarming, an increase in reactive oxygen species (ROS) (Camara et al 2003, Riess et al 2004, decreased ATP synthesis and damaged mitochondrial ultrastructure (Tveita et al 1996a, Aupperle et al 2007) have been reported. Such findings are signs of alterations in mitochondrial function, which again likely affects cardiac contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated [Ca 2+ ]cyt increases energy consumption by activating ATP-dependent cross-bridge cycling, and ATP-dependent Ca 2+ pumps in the SR and sarcolemma (14). The hypothermia-induced increase in ATP consumption will eventually cause mitochondrial depolarization, an uncoupling of oxidative phosphorylation, ROS formation, compromised energy production, mitochondrial swelling, and cell death (6,14,30,40,42,70,72,78,88,105,154,155,184,198,199). Using electron microscopy and morphometry, we were able to quantify and categorize myocardial mitochondrial damage after rewarming following a 4-h period at 15-13°C with spontaneous circulation (200).…”
Section: Accidental Hypothermia/rewarming -The "Ugly"mentioning
confidence: 99%
“…Possible future application could be facilitating donor management and further evaluation of marginal donor hearts. [10][11][12] Immunosuppressive Therapy: Pharmacodynamics Due to Prof. Mohr's initiative, our group showed increased interest in the pharmacodynamics of immunosuppressive therapy. Without proper immunosuppressive therapy, solid organ transplantation is not feasible.…”
Section: Transplantation Programmentioning
confidence: 99%